El fondo complementario de jubilación minera, metalúrgica y siderúrgica, y su inexigibilidad frente a los convenios de estabilidad jurídica - Salazar Benza, Juan Manuel (2013)
In order to attract necessary investment for the development of our country, the Peruvian State signed agreements of legal stability with various mining companies, for the purpose of not altering the legal regime of the income tax for a certain period. However, is there an exception? Which are the scopes of these agreements? Guided by the principles and basic concepts of Tax Law, the authors will study the nature of the Fondo Complementario de Jubilación Minera, Metalúrgica y Siderúrgica, determining if it leads to an infringement of legal stability agreements signed by the Peruvian State.